Tradisi Jenang Suro Sebagai Pengikat Solidaritas Sosial: (Studi Di Kampung Krupuk Karang Mluwo Kecamatan Kaliwates Kabupaten Jember) - Efendi, Faizal (Institut Agama Islam Negeri Fattahul Muluk Papua, 2021)
This study aims to investigate the Jenang Suro Tradition in Krupuk Karang Mluwo, Mangli Village, as a hereditary tradition transmitted by their ancestors and performed on a continuous basis when the month of Suro comes. Jenang suro is not only regarded as a tradition, but also as a symbol of community solidarity. This research applies an anthropological approach and applies a qualitative research method. The following findings of this research: The jenang suro ritual transmitted down through generations by the ancestors of the krupuk village community which is consistently found when the month of suro begins, with the intention of rejecting reinforcements and expressing thankfulness for Allah SWT's presence. This ritual is seen as a social binder by the community. The village community asks a religious leader or ustadz to lead the prayer procession after jenang's production process, and the last step is Ter-Ater (delivering) jenang suro to the neighbors. This procedure intends to be a sort of sodaqoh from jenang that has been made, as well as a binder of their neighborly unity.